Microsatellite markers in common bean (Phaseolus vulgaris L.) - Monika VIDAK; Klaudija CAROVIĆ-STANKO; Ana BAREŠIĆ; Martina GRDIŠA; Zlatko ŠATOVIĆ; Zlatko LIBER (Journal of Central European Agriculture, 2017)
Common bean is one of the most cultivated and consumed grain legumes worldwide, showing a high level of genetic diversity. Here is presented a detailed review of development and mapping of simple sequence repeats (SSRs, microsatellite markers) in the common bean. In the last 25 years, common bean has been the subject of numerous genetic studies, in which the identification and use of SSRs were conducted, and lead to the development of genetic maps. First genetic maps of common bean have been developed in the 1990s and were based on different molecular markers, and included domestication genes and important agronomic traits. Later, SSRs allowed the genetic mapping of more narrow crosses that are often of interest in plant breeding. Most genetic maps have been correlated with the core map established in the recombinant inbred population BAT93 x Jalo EEP558, and includes different markers, RFLP (restriction fragment length polymorphism), RAPD (random amplified polymorphic DNA), AFLP (amplified fragment length polymorphism), and SSRs in particular. More than 2,000 SSR markers are available for the common bean and they are an important tool to evaluate the genetic diversity of common bean landraces. SSRs are also useful to evaluate intra-specific diversity within the genus Phaseolus.